2003
DOI: 10.1354/vp.40-2-143
|View full text |Cite
|
Sign up to set email alerts
|

Detection Rates of Porcine Reproductive and Respiratory Syndrome Virus, Porcine Circovirus Type 2, and Swine Influenza Virus in Porcine Proliferative and Necrotizing Pneumonia

Abstract: A retrospective study on pig lung tissues from 60 cases of proliferative and necrotizing pneumonia (PNP) was performed to determine the presence of porcine reproductive and respiratory syndrome virus (PRRSV), swine influenza virus (SIV), and porcine circovirus type 2 (PCV2) in these lesions. Cases selected included 30 cases diagnosed between 1988 and 1992 and 30 cases diagnosed between 1997 and 2001. In each group of 30 cases, 10 were from suckling piglets, whereas the other 20 were from postweaned animals rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 15 publications
3
43
0
6
Order By: Relevance
“…The results of the present study therefore suggest that the major aetiological agents of PNP in Italian pigs are PRRSV and PCV2, as previously documented in Canadian (Drolet et al, 2003) and European (Pesch et al, 2000;Grau-Roma and Segale´s, 2007) studies. However, the results of our investigation are more aligned with those of the Canadian study, in which PRRSV infection was more consistently demonstrated, rather than the European study that suggested a dominant role for PCV2 infection in PNP.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The results of the present study therefore suggest that the major aetiological agents of PNP in Italian pigs are PRRSV and PCV2, as previously documented in Canadian (Drolet et al, 2003) and European (Pesch et al, 2000;Grau-Roma and Segale´s, 2007) studies. However, the results of our investigation are more aligned with those of the Canadian study, in which PRRSV infection was more consistently demonstrated, rather than the European study that suggested a dominant role for PCV2 infection in PNP.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is not dissimilar to those of other investigations. Grau-Roma and Segale´s (2007) detected no agents in eight out of 74 cases (10.8%) and Drolet et al (2003) described four out of 60 samples (7%) as negative for all agents for which they tested. The relatively higher percentage of negative samples in the present study probably reflects the smaller number of agents investigated.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations